Evaluation of microwave-assisted digestion condition for the determination of metals in fish samples by inductively coupled plasma mass spectrometry using experimental designs - Low, K.H.; Abas, M.R.; Zain, Sharifuddin Md (2012)
This paper describes the development of a compromised single-stage microwave-assisted digestion condition for multi-element determination in fish samples by inductively coupled plasm: mass spectrometry using experimental designs. A Plackett-Burman design was carried out as a multivariate strategy to investigate the main effects of the following parameter on microwave-assisted nitric acid digestion: microwave irradiation time, ramp time, digestion temperature, microwave power limit and the addition of hydrogen peroxide or hydrochloric acid. The most significant microwave setting parameters (radiation time, ramp and temperature) were further evaluated by response surface methodology under Box-Behnken design, while others were kept constant. The influences of different parameters vary according to metal element, thus the working conditions were established as a compromise within optimum region found for each targeted element which ensures quantitative recoveries and time efficiency. The compromised conditions are: ramp to 185°C in 10.5 min then hold for 14.5 min with 1600W (50%) of microwave power, using reagent mixture composed of 2.5 mL nitric acid, 0.5 mL hydrochloric acid and 7.0 mL water. Good agreements were demonstrated between measured and certified values with respect to DORM-3, DOLT-4 and ECM-CE278 and this method was successfully applied for metals determination in tilapia tissues. © 2012 Copyright Taylor and Francis Group, LLC.